Atención al cliente en el almacén Don Pato Jr. de la ciudad de Babahoyo, en el periodo 2023. - Cabezas Verdezoto, Katiusca Yamilex (2025)
The Don Pato JR Warehouse, located in Babahoyo, has faced various challenges in managing its customer service during 2023, which has negatively impacted its reputation and customer loyalty. This case study focused on analyzing the factors that influence the quality of customer service in the warehouse, in order to identify the main deficiencies, evaluate customer satisfaction and propose improvement strategies. Through surveys applied to 60 frequent customers, recurring problems are identified, such as the lack of clear protocols for managing incidents, especially in situations such as the loss of items. In addition, a perception of low willingness of staff to solve problems effectively and quickly will be observed. The results showed that, although a considerable proportion of customers rated the service received positively, there is a significant number who perceive areas for improvement, especially in the speed of response and in the management of incidents. These deficiencies directly impact customer satisfaction and, therefore, loyalty. Based on these findings, it was recommended to implement ongoing training for customer service staff, establish clear protocols for problem management, and create a structured feedback system that allows services to be tailored to customer needs. These actions will not only improve the customer experience, but will also contribute to strengthening Don Pato JR's competitiveness in the local market.